1988
DOI: 10.1159/000234615
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Systemic and Mucosal Immune Responses to Inhaled Ragweed Antigen in Experimentally Induced Infection with Respiratory Syncytial Virus Implication in Virally Induced Allergy

Abstract: Groups of BALB/c mice were either sham-infected or infected intranasally with respiratory syncytial virus (RSV). On the third day following intranasal inoculation, all groups of mice were exposed by inhalation to ragweed antigen for 5 consecutive days and rechallenged with ragweed on day 31. Development of antibody activity to ragweed antigen was examined in serum and bronchial washings at regular intervals employing an ELISA assay for IgG and IgA antibody activity and passive cutaneous anaphylaxis for IgE-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 6 publications
2
28
1
Order By: Relevance
“…The RSV G protein especially mounts an IgE response (33,34). Several investigators reported allergen-specific IgE enhancement in animals with prior RSV (35,36), influenza (37), or parainfluenza-3 viral (38) infection, suggesting that the virus-induced increase in allergen-specific IgE is possibly due to the facilitation of allergen uptake by virally damaged epithelial cells. It is likely that an increase in Df-specific IgE was not detected in the present study because mice were first sensitized and challenged with allergen and subsequently infected with RSV.…”
Section: Discussionmentioning
confidence: 99%
“…The RSV G protein especially mounts an IgE response (33,34). Several investigators reported allergen-specific IgE enhancement in animals with prior RSV (35,36), influenza (37), or parainfluenza-3 viral (38) infection, suggesting that the virus-induced increase in allergen-specific IgE is possibly due to the facilitation of allergen uptake by virally damaged epithelial cells. It is likely that an increase in Df-specific IgE was not detected in the present study because mice were first sensitized and challenged with allergen and subsequently infected with RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the phenomenon of allergen sensitization via the lung as a result of coincidental exposure to environmental "adjuvants" or infectious agents has also been previously described. Among the infectious factors that may contribute to permanent IgE sensitization are respiratory syncytial virus (RSV) (47)(48)(49)(50)(51), Rhinovirus (52,53), Bordetella pertussis (54 -57), and EBV. In addition, the ability of environmental factors to alter the development of IgE tolerance such as exposure to smoke, diesel particles, or ozone has been described (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that RSV infection can enhance the development of sensitization and the magnitude of antibody responses to other inhaled allergens found concomitantly in the respiratory tract during acute infection [38,39].…”
Section: Infectionsmentioning
confidence: 94%